Purification of an alpha amylase from Aspergillus flavus NSH9 and molecular characterization of its nucleotide gene sequence - Karim, Kazi Muhammad Rezaul; Husaini, Ahmad; Sing, Ngieng Ngui; Sinang, Fazia Mohd; Roslan, Hairul Azman; Hussain, Hasnain (Springer Verlag, 2018)
In this study, an alpha-amylase enzyme from a locally isolated Aspergillus flavus NSH9 was purified and characterized. The extracellular α-amylase was purified by ammonium sulfate precipitation and anion-exchange chromatography at a final yield of 2.55-fold and recovery of 11.73%. The molecular mass of the purified α-amylase was estimated to be 54 kDa using SDS-PAGE and the enzyme exhibited optimal catalytic activity at pH 5.0 and temperature of 50 °C. The enzyme was also thermally stable at 50 °C, with 87% residual activity after 60 min. As a metalloenzymes containing calcium, the purified α-amylase showed significantly increased enzyme activity in the presence of Ca2+ ions. Further gene isolation and characterization shows that the α-amylase gene of A. flavus NSH9 contained eight introns and an open reading frame that encodes for 499 amino acids with the first 21 amino acids presumed to be a signal peptide. Analysis of the deduced peptide sequence showed the presence of three conserved catalytic residues of α-amylase, two Ca2+-binding sites, seven conserved peptide sequences, and several other properties that indicates the protein belongs to glycosyl hydrolase family 13 capable of acting on α-1,4-bonds only. Based on sequence similarity, the deduced peptide sequence of A. flavus NSH9 α-amylase was also found to carry two potential surface/secondary-binding site (SBS) residues (Trp 237 and Tyr 409) that might be playing crucial roles in both the enzyme activity and also the binding of starch granules. © 2018, Springer-Verlag GmbH Germany, part of Springer Nature.